1997
DOI: 10.1143/jpsj.66.3617
|View full text |Cite
|
Sign up to set email alerts
|

Spin Dynamics of the One-DimensionalJ-J' Model and Spin-Peierls Transition in CuGeO3

Abstract: Spin dynamics as well as static properties of the one-dimensional J-J ′ model (S = 1/2, J > 0 and 0 ≤ α = J ′ /J ≤ 0.5) are studied by the exact diagonalization and the recursion method of finite systems up to 26 sites. Especially, the dynamical structure factor S(q, ω) is investigated carefully for various values of α. As α increases beyond the gapless-gapful critical value αc = 0.2411, there appear features definitely different from the Heisenberg model but the same with the Majumdar-Ghosh model. Some of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 59 publications
(104 reference statements)
9
56
0
Order By: Relevance
“…The size dependence of the residues in both regions of wave numbers is quite similar to that for the excitation continua of the S = 1/2 [30] and 1 [9] isotropic Heisenberg chains. The behavior of the residue around q = 0.9π at α = 0.7 is different from that in the other wave numbers.…”
Section: A Haldane Phasesupporting
confidence: 60%
See 2 more Smart Citations
“…The size dependence of the residues in both regions of wave numbers is quite similar to that for the excitation continua of the S = 1/2 [30] and 1 [9] isotropic Heisenberg chains. The behavior of the residue around q = 0.9π at α = 0.7 is different from that in the other wave numbers.…”
Section: A Haldane Phasesupporting
confidence: 60%
“…Note that the finite-size effects only for the residues are presented, since the positions of the poles scarcely depend on the system size. We discuss the results, making reference to the typical size dependence of the excitation continua for the S = 1/2 [30] and 1 [9] isotropic Heisenberg chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences are consistent with the previous studies on the spin DSF. 2,22) The spin DSF in the dimer phase seems to capture the exper- imental features of CuGeO 3 15) showing large weights around k = π/2 and at the upper edge of the continuum. Note that we cannot see the splitting of the lowest-energy excitations from the continuum, i.e., the bound state of two spinons in the dimer phase.…”
Section: Numerical Resultsmentioning
confidence: 91%
“…On the contrary, recent studies have shown that the spinPeierls state is not stable at zero temperature with phonons in the antiadiabatic limit. [1][2][3][4] At the same time, these studies have shown that there is a critical coupling of the transition between these states. Namely, for the coupling constant α < α c , the ground state is the spin-liquid state, but for α > α c , it is the spin-Peierls state.…”
Section: Introductionmentioning
confidence: 87%